Efeitos da quantização magnética nas transições ópticas de poços quânticos no regime de temperatura ambiente - Oliveira, Vinicius Andrade de (2025)
Efforts from the scientific community have been devoted to the development and incorpora tion of high-quality semiconductors into different applications. A large part of this effort was focused on growth techniques, through molecular beam epitaxy, enabling the fabrication of nanostructures such as quantum wells. Along the materials used for nanostructures growth, Gallium Arsenide (GaAs) stands out, as this binary offers high versatility and compatibility with other III-V compounds. Among the scientific advances made, currently, the technology available allow the application of techniques, like magnetophotoluminescence in differents temperatures range with high thermal and mechanical stability, enabling the investigation of these structures in a way that was not accessible until recently. In the present work, we investigate the energy levels of quantum wells GaAs/AlGaAs grown on a GaAs substrate with different orientation using magnetophotoluminescence technique. The results reveal optical transition associate with the energy levels of the transition electron-heavy hole and electron light-hole at 0 Tesla. Increasing the magnetic field induced the emission of two new energy levels that had not yet been observed at room temperature. The first transition inovelves an electron and the second heavy-hole level, showing invariance in spin polariza tion. The second transition exhibited asymmetric behaviour, for spin up polarization, the level corresponds to electrons recombinin with the first Landau level of light holes, while for spin down polarization, it was associated with the transition between electrons and the third Landau level of heavy holes. Therefore, the magnetophotoluminescence technique applied at room temperature allowed the direct measurement of excited levels and the asymmetry in the emission of a specific spin population, which had no yet been reported.